Mechanosensing and Plant Growth Regulators Elicited During the Thigmomorphogenetic Response - Telewski, Frank W. (Frontiers in Forests and Global Change, 2021)
The influence of mechanical bending or flexing of trees due primarily to wind, on tree growth and development has been observed and reported for hundreds of years. This response was defined as the thigmomorphogenetic response in 1973. In general, the response of trees to bending is a reduction in extension/height growth, and increase in radial growth and increased allocation from above ground to below ground tissues accompanied by changes in biomechanical properties of the xylem. Within the last fifty years, significant advancements have been reported in characterizing the response of trees to this mechanical. Current research has advanced the understanding of how trees respond after mechanoprecption via molecular signaling and physiological changes in growth regulation. This review provides insight into these subcellular reactions of thigmomorphogenesis and a summary of recent advances in understanding the response of trees to mechanical bending.